Migration forcée et vulnérabilité éducative Parcours et expériences de familles désplacées et (dé)scolarisation de leurs enfants - Sanchez-Mazas, Margarita (Cohésion sociale et pluralisme culturel, 2022)
Forced displacement invariably entails jeopardizing education. By giving parents and children a voice, this study examines the inextricable situations - wars, repressions, humanitarian crises - forcing them into exile. It retraces the paths of children marked by dropping out of school or chaotic schooling in the countries of origin or transit. It reveals the challenges posed by the arrival of this population of particularly vulnerable pupils for the educational and social work of schools. By questioning the limitations of the right to education in the context of forced migration and a restrictive asylum policy, this book fills an important gap in the study of educational vulnerability linked to exile. It offers innovative ways to support the schooling of children of asylum seekers, by enabling them to take advantage of their own, often unsuspected, resources.